A new macroeconometric approach to the NATREX model of the equilibrium real exchange rate. (18th November 2009) - Dikmen, Nedim
This paper shows a new macro-econometric approach to the NATREX model of the equilibrium real exchange rate. Many of the models in the literature are based upon anticipations, monetary policy, and speculative capital movements. The NATREX model denotes what are the fundamental determinants of the equilibrium real exchange rate R(Z) and the convergence process – the terms in braces in actual real exchange rate equation. The NATREX model is very different from the monetary models with anticipations and from PPP. The logic of the NATREX model is an analytical framework whereby one can analyse the medium- and long-run effects of policies and exogenous variables upon the real exchange rate and external debt/GDP ratio. This is positive economics. The fundamentals (Z, δ) are treated as exogenous or control/policy variables. The basic equations are derived from inter-temporal optimisation when there is uncertainty, using optimal control and dynamics programming. The NATREX depends on productivity which drives investment in the short run but growth and savings in the long-run.